Food, atmospheres and olfactory aestheticizations - Mancioppi, Elena (E|C, 2020)
With the aestheticization of goods and spaces typical of advanced capitalism, we are witnesses of an invasiveness of the olfactory atmospheres related to food. Food aromas, mostly of synthetic processing, are part of sophistication practices that set in motion a complex series of perceptual, emotional and social dynamics which reverberate on the ways in which the community relates to food and its environment. Smells will therefore be interpreted as vectors of political messages, more or less direct. Through an esthesiological, aesthetic and phenomenological perspective, the peculiarities, consequences and inconsistencies of the contemporary Western scented atmosphere, symptomatic of a broader model of management of common living, will be highlighted.